2008
DOI: 10.1002/ibd.20348
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of dietary curcumin in mouse model of chemically induced colitis are strain dependent

Abstract: The efficacy of dietary curcumin in TNBS colitis varies in BALB/c and SJL/J mouse strains. Although the exact mechanism underlying these differences is unclear, the results suggest that the therapeutic value of dietary curcumin may differ depending on the nature of immune dysregulation in IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 52 publications
1
65
0
Order By: Relevance
“…• Inhibited the TNBS-induced colitis and splenocyte proliferation in BALB/c mice but not in NKT-deficient SJL/J mice (Billerey-Larmonier et al, 2008).…”
Section: Psoriasismentioning
confidence: 98%
See 1 more Smart Citation
“…• Inhibited the TNBS-induced colitis and splenocyte proliferation in BALB/c mice but not in NKT-deficient SJL/J mice (Billerey-Larmonier et al, 2008).…”
Section: Psoriasismentioning
confidence: 98%
“…Numerous reports have been published suggesting that oral administration of curcumin down-regulates TNF-a expression both in the serum and in the tissue of animals (Nanji et al, 2003;Yao et al, 2004;Sharma et al, 2007a;Billerey-Larmonier et al, 2008;Larmonier et al, 2008;Ung et al, 2010;El-Moselhy et al, 2011;Gutierres et al, 2012) ( Table 2). Attenuation of TNF-a levels by curcumin has been noted in mice (Leyon and Kuttan, 2003), rats (Siddiqui et al, 2006) and rabbits (Yao et al, 2004;Huang et al, 2008).…”
Section: Suppression Of Tnf By Curcumin In Vivomentioning
confidence: 99%
“…Up to 8 g daily administered to patients for 3 mo did not cause toxicity (9). In our previously published studies, dietary curcumin supplementation leading to colitis prevention resulted in millimolar concentrations within the colonic lumen with no observable toxicity (6,26). However, in both humans and laboratory rodents, curcumin displays very low bioavailability with poor absorption and rapid metabolic elimination (3).…”
mentioning
confidence: 97%
“…Our laboratory has extensively studied the anti-inflammatory benefits of curcumin in murine IBD models. [17][18][19] More recently, we also demonstrated that curcumin inhibits colon cancer cell migration through physical interaction with and activation of PTPN1 tyrosine phosphatase to reduce the abnormally hyperphosphorylated and hyperactive form of cortactin, a protein implicated in cancer motility and tumor invasiveness. 20 We hypothesized that due to its poor bioavailability, orally administered curcumin as a dietary supplement targets and impacts primarily epithelial cells and the gut microbiota, and that curcumin may modulate colonic microbial ecology and prevent the progression of chronic colitis to CAC.…”
Section: Introductionmentioning
confidence: 99%